Digital Literacy as The Basis for The Use of Digital Wallets during COVID-19 Pandemic - Darmawan, Marzuki; Wenerda, Indah (CHANNEL: Jurnal Komunikasi, 2022)
This research aims to find out how far students in Yogyakarta carry digital literacy as the basis for using their e-wallets. An E-wallet is one of the cashless payment tools currently a means of payment that is widely used by the people of Indonesia, especially the younger generation. Students, as part of the younger generation, often use e-wallets as a means of payment instead of cash. Students have a basic knowledge of digital wallets from experience and the information they get from their environment. The basis of expertise is digital literacy by students using e-wallets.  This research uses a qualitative research method with resource sampling and purposive techniques. Researchers used data collection techniques with interviews and document studies to find data from sources. Then the data can be tested by triangulation of the data source. This research results in students actively using digital wallets in online transaction activities. From this practice, if referring to digital literacy competencies using ten JAPELIDI competencies in four quadrants, functional and critical consuming quadrants are the most dominant carried out by students. At the same time, the other quadrant has yet to be done by students using digital wallets.